Osteoporosis of Crohn’s Disease: A Critical Review - Neena S Abraham; Richard N Fedorak (Canadian Journal of Gastroenterology)
Osteoporosis has long been a recognized complication of Crohn’s disease (CD), with a documented incidence ranging from 31% to 65%. The cause of osteoporosis in Crohn’s patients is likely multifactorial; corticosteroids, inflammatory cytokines, small bowel resection and the resultant calcium and vitamin D deficiencies, hypogonadism, malnutrition and the cachexia of inflammation all play a role. However, the mechanism responsible for osteoporosis associated with CD remains unclear. Treatment of decreased bone density in CD patients has been limited to calcium and vitamin D replacement. The present understanding of the pathophysiology, mechanism and treatment of osteoporosis in CD is reviewed, with the focus on the role of steroid-induced osteoporosis and the use of bisphosphonates.